PENGARUH PERAWATAN BETON YANG BERBEDA-BEDA TERHADAP KEKUATAN BETON - Yulfalentino; Bintarto Purwo Seputro (J-Innovation, 2018)
A fews points to get high quality of asphalt concrete are mixing, casting, compacting, and curin. The other things are supporting of matters such as form-work. The curing will being as step to do the asphalt concrete , developing them to be perfect hardly. The process of curing are maintanance of humadity , temperature, surface at asphalt concrete and time line periode. The research done past time, the more do the maintanace periodely increasing to be more higher pressure value , and the others things of it (Yurmansyah Indra, 2001). So, the researcher had done with many variaties of comparing each others of them. We have got the difference power of the maximum asphalt concrete . Likes ; do the maintanance by watering wet 3 times in a day BU5) = 195,28 kg/cm2,by the wet burlap3 times in a day (BU4) = 188, 33 kg/cm2. With wet on water ,2 - twice in a day (BU3) = 181,11 kg/cm2. Without do the maintanaance , (BU2) = 165, 56 kg.cm2. by nature , (BU1) = 152,27 kg/cm2. Those meaning are the average-power of higher pressure asphalt concrete with or witout maintaning are 15 – 16 % as the conclusions.